Genetic factors exist behind the high prevalence of reduced high-density lipoprotein cholesterol levels in the Roma population - Pikó, Péter; Fiatal, Szilvia; Kósa, Zsigmond; Sándor, János; Ádány, Róza (Atherosclerosis, 2017)
Previous findings showed that reduced plasma high-density lipoprotein cholesterol (HDL-C) levels are more frequent in all age groups of the Hungarian Roma compared to the general population. It suggests that genetic factors may exist behind this phenomenon. Our present study was designed to test this hypothesis, i.e., to define whether genetic factors contribute to the higher prevalence of reduced HDL-C among Roma. Single nucleotide polymorphisms (N = 21) contributing to the variation in plasma HDL-C concentrations were analysed in the Hungarian Roma (N = 646) and general (N = 1542) populations. Genetic risk scores, unweighted (GRS) and weighted (wGRS), were computed and compared. Associations between the GRSs and the prevalence of reduced HDL-C levels were analysed. The GRS and wGRS were significantly higher in the Roma compared to the general population (GRS: 22.2 ± 3.2 vs. 21.5 ± 3.3; wGRS: 0.57 ± 0.1 vs. 0.53 ± 0.1; p<0.001). One half per cent of Roma subjects were in the bottom fifth of the wGRS (wGRS≤ 0.3) compared with 1.8% of those in the general population (p=0.025), while 5% of the Roma subjects were in the top fifth of the wGRS (wGRS≥ 0.75) compared with 2.6% of those in the general population (p=0.004). The GRS showed similar correlation with reduced plasma HDL-C levels in the two populations, whilst the wGRS showed stronger correlation with the trait among Roma after controlling for confounders. These results strongly suggest that genetic factors contribute to the higher prevalence of reduced HDL-C levels among Roma, so interventions aiming to improve Roma health status need to consider their increased genetic susceptibility. •Genetic background of reduced HDL-C levels among Roma was firstly investigated.•Genetics plays a part in the very high prevalence of reduced HDL-C values among Roma.•Majority of the susceptibility alleles were accumulated in the Roma population.•Interventions to improve Roma health need to consider the genetic susceptibility.